Analysis of spatial heterogeneity and driving factors of capital allocation efficiency in energy conservation and environmental protection industry under environmental regulation. (February 2020) - Geng, Chengxuan; Cui, Zongying
Abstract: The paper integrates the economics and geography theoretical methods, and takes the data of 119 Chinese A-share listed companies in the energy conservation and environmental protection industry from 2008 to 2017 as the research sample, analyzes the spatial heterogeneity of industrial capital allocation efficiency and its driving factors from the perspective of environmental regulation. The GWR model is constructed to study the effect of driving factors on the capital allocation efficiency of each province and visualize the spatial distribution state of driving factors. The results show that the capital allocation efficiency of China's energy conservation and environmental protection industry shows a trend of increasing volatility, but there are obvious spatial dynamic differences in different provinces. Environmental regulation has a significant positive impact on regional capital allocation efficiency and enhances the effect and spatial heterogeneity of other drivers. Infrastructure condition and financial development have a significant positive effect on regional capital allocation efficiency, and both tend to decline from east to west. While the government support has a low impact and the scope of fluctuation and spatial heterogeneity is small, indicating that the relevant government support policies still lack the pertinence and effectiveness of local conditions. Highlights: Pollution promotes the strengthening of China's environmental regulation. Environmental regulation promotes the development of sample industry in China. The development of sample industry in China has obvious spatial heterogeneity. Environmental regulation aggravates the effect of other driving factors.